Design And Development Of An Automated Sorting System In Manufacturing Industries - Azinuddin Akmal, Abdul Aziz (UTeM, 2010)
Design and development of the automated sorting system in manufacturing industries for plastic recycling was done by conducting research on the method of identification plastic types and sorting mechanism. Plastic that usually used can be categorized into seven types. There are two main types of sorting system which are marcosorting and microsorting. Research methodology for this project also has been explained. Methods used to perform research are archival collection including online and library research. Besides, methods to design and analysis the proposed design by using CATIA software also stated. In order to achieve the objectives of the project, the studies and research on the existing designs of the automated sorting system for plastic recycling were done. The advantages and disadvantages of each existing design were reviewed and the data will be used for development of a new design. The design process is started by concept generation and selection. The conceptual designs produced are selected by using concept screening. Concept design selected then been continued for development of detail design by using CATIA software. The detail design is analysis is Generative Structural Analysis workbench in CATIA to find the Von Mises stress and determine the factor of safety. The proposed design has saved about 92 percent of space usage compare to the existing design. The proposed design is compared to the existing design to find out the advantages and disadvantaged of the proposed design. Design optimization also been explained in the discussion section.